Influence of pre-slaughter capture chase duration stress on carcass and meat quality of indigenous chicken reared under traditional system in Benin - BONOU, ASSOUAN GABRIEL; AHOUNOU, GBÊNAGNON SERGE; SALIFOU, CHAKIRATH FOLAKÊ ARIKÊ; BACHABI, KENETH; PARAISO, FIDELE H.; KONSAKA, BERNADETTE M.; DAHOUDA, MOHAMADOU; DOUGNON, TOSSOU JACQUES; FAROUGOU, SOUAÏBOU; YOUSSAO ABDOU KARIM, ISSAKA (My University, 2017)
The current study aims to evaluate the influence of the pre-slaughter capture chase duration stress on carcass and meat quality in local chicken of Benin. Sixty-four chickens of 6 to 7 months old divided into 4 flocks of 8 males and 8 females each reared under traditional system were used. Chickens of first group were not chased before slaughter. Whereas, chickens of the second, the third and the fourth groups were slaughtered respectively after 5 minutes, 10 minutes and 15 minutes of chase by 3 persons. Carcass and meat quality was evaluated. Carcass quality traits didn’t vary according to the preslaughter capture chase stress. The two longer capture chase duration chickens had the lower breast pH at the first measure time. But it was higher in those chased during 15 minutes at 48 hours after slaughter. Control birds showed lower pH than the 5 minutes stressed one at 1 and at 12 hours. The thigh pH values were higher with the most chased chickens. However, drip loss at 24 hours after slaughter didn't vary. The breast lightness was higher in the most chased on the slaughter day. Meanwhile, the breast yellow index was higher with chickens of 15 minutes of chase. But no difference was found for the meat red index values of the four flocks. The meat flavor, juiciness, tenderness and global acceptance didn't vary according to the preslaughter capture chase stress. In sum, the sensory and technological meat qualities of local chickens decrease more with the capture chase duration stress
Keywords: Indigenous chicken; capture chase; meat; quality; Benin.